A Python-Based Indoor Channel Model with Multi-Wavelength Propagation for Color Shift Keying - Gutiérrez, Juan F.; Sandoval, Diego; Quintero, Jesus M. (Photonics, 2024)
Color shift keying is a modulation scheme for visible light communication that uses fixtures with three or more narrow-spectral light-emitting diodes to transmit data while fulfilling the primary function of illumination. When this modulation is used indoors, the reflectivity of the walls strongly affects the inter-channel interference and illumination quality. In this paper we present an indoor channel model that takes into account multi-wavelength propagation. This model is available as an open-source Python package. The model calculates the inter-channel interference, illuminance, correlated color temperature, and color rendering index at the receiver position. The Python package includes a module for estimating the symbol error rate. To validate the model, we computed the received power at each color photodetector for four different indoor scenarios. The model demonstrated a color rendering index of less than 15 when using IEEE-based color shift keying and non-uniform illumination on a horizontal plane. The simulation determined the required luminous flux to achieve a symbol error rate of less than 10−5 when the photodetector is at the center of the indoor space and vertically below the light source. To maintain a symbol error rate less than 10−5, the luminous flux increases when the photodetector is displaced in a diagonal direction from the center of the plane.